Stress Adaptation Model For Uncertain Process Of Diabetes Mellitus Disease - Arif Budiman, M. Elyas; Yusuf, Ah; Sri Suhardiningsih, Av; Endang Nihayati, Hanik (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction: Uncertainty Diabetes mellitus shows the inability of individuals to determine the meaning of events related to the disease process. Uncertainty Diabetes mellitus causes stress due to uncertainty around the disease, disease process, treatment and side effects. The purpose of this study was to develop a stress adaptation model to the uncertainty of the diabetes mellitus disease process. Method: The design of this research is an explanatory survey with a cross sectional approach.Methods: The sample size of the study was 250 Diabetes mellitus clients who were recruited using simple random sampling technique. The research variables are cognitive, biophysical, social, psychological factors, structure providers, illusions, inferences, uncertainty, psychosocial coping and adaptations. Data were collected by questionnaire and analyzed by SEM-PLS. Results: The results of this study indicate that cognitive, biophysical, psychological factors, structure providers and the illusion of inference have a significant effect on uncertainty. Social factors have no effect on uncertainty. Uncertainty has a significant effect on coping and psychosocial adaptation. Coping has a significant effect on psychosocial adaptation. The test criteria state that if the T-statistics T-table value (1.96) or the P-value <significant alpha 5% or 0.05, it is stated that there is a significant effect of the independent variable on the dependent variable. Conclusions: The finding of the stress adaptation model to the uncertainty of the disease process Diabetes mellitus is associated with that uncertainty is a cognitive condition, indicating the inadequacy of existing cognitive factors to support the interpretation of disease-related events.Then adaptation in the context of uncertainty reflects the continuation of the normal biopsychosocial behavior of Diabetes mellitus clients and is the expected result of coping efforts to reduce uncertainty which is assessed as a danger.